Disposal pattern of young Sahiwal cattle under organized farm - UPADHYAY, ARPAN; SADANA, D K; GUPTA, A K; CHAKRAVARTY, A K; SINGH, A; M, MANOJ; MAHER, D (The Indian Journal of Animal Sciences, 2015)
Data of 830 female Sahiwal calves, born between 1986 and 2009 at National Dairy Research Institute’s Farm, were analysed to study the influence of different non-genetic factors on disposal pattern (mortality and culling) of young Sahiwal cattle up to age at first calving (AFC) under organized herd. Different non-genetic factors like season of birth, period of birth and birth weight of calves were considered to assess their influence on mortality and culling. Overall disposal up to AFC was 33.78%, comprising 24.67% due to mortality and 9.11% due to culling. Maximum mortality was observed during first month of age, which was attributed to higher incidence of pneumonia and enteritis encountered in this age group. Mortality rate revealed a decreasing trend along with the age. Maximum culling rate was found during 12 month to AFC age group. Season of birth had highly significant influence on incidence of mortality during first month of age, whereas period of birth had significant influence on incidence of culling during 12 month to AFC age group. Birth weight of calves had no significant influence on either culling or mortality. The likelihood of mortality was higher in rainy and winter season born calves. The overall results showed that the major reason of female calves’ disposal was mortality, especially during first month of age. Therefore, intensive care of calves of this age group against inclement weather conditions by providing better feeding and management would result in reducing mortality rate in calves.